THE RELATIONSHIP BETWEEN MORPHOLOGICAL AWARENESS AND ENGLISH VOCABULARY KNOWLEDGE OF SIXTH SEMESTER STUDENTS IN IKIP MATARAM - Baiq Sumarni (Universitas Pendidikan Mandalika, 2016)
This study focuses on finding the relationship between morphological awareness and English vocabulary knowledge of Sixth semester students in IKIP Mataram. Many researchers have conducted a number of studies to find out the most effective strategies in learning vocabulary. One of them which is discussed in this study is applying morphological awareness. The first research problem is talking about the English vocabulary size of the students. The second problem is talking about the level of the students’ morphological awareness. and the third problem is talking about the relationship between morphological awareness and the English vocabulary size of sixth semester students in IKIP Mataram. In turn, in conducting this research, the researcher uses a mixed methods. Not only quantitative analysis, descriptive statistics and other statistical tests, but also qualitative analysis are used. The data presents the students’ vocabulary size in the form of level which is adapted from the theory by Nation and Beglar (2007) and also their morphological awareness in form of level which is adapted from the theory by McBride-Chang et al (2005). This data also presents the relationship between morphological awareness and English vocabulary knowledge in form of correlation based on Pearson product-moment formula. This analysis shows that the sixth semester students in IKIP Mataram are in level 6,000 means that their results is good enough based on Beglar and nation (2007). And the results of the morphological awareness are variant. Thence, this study also found that there is relationship between the students’ vocabulary size and their morphological awareness.